The Development Of Religious Humanistic Education In Tegalrejo Datinawong, Babat Lamongan - Khotimatus Sholikhah; Sulhatul Habibah; Khoirotun Ni'mah (STAI Miftahul Ula Nganjuk, 2018)
Indonesia Society is currently faced with a moral crisis, whether it occurs in young children, adults up to the parents. Morale is greatly needed by the community, in the form of religious humanist communities that are far from the attitude of rebellion, criminality, and selfishness. However, the reality as it is still far from the expectations of society. This is due to many things one of which is a lack of awareness in education, parenting parents are not good, and the bad environment. This is contrary to the notion of humanistic education. Humanistic Education upholds human values capable mencipkan dynamic society there is no issue that destroys human dignity. In this case, the author want to learn about the development of the religious humanist education in the community. The point of this study was Tegalrejo Datinawong district, Tripe regency, Lamongan. Community development humanist religious: first, the people who develop humanity values (honesty, compassion, fairness and mutual respect) and remain in a religious framework in accordance with religious values (habluhablum, hablu minal nature and habluminallah), Second, deciding religious humanist communities were starting from community leaders or leaders who were in the village Tegalrejo, among other village leaders, clerics, religious teacher/cleric as a motivator. Third, measures to develop human society among other religious communities develop positive values, teach moral message to the community, until finally awakened humanist and religious communities.